CHEMICAL COMPOSITION AND ANTIOXIDANT ACTIVITY OF MATRICARIA CHAMOMILLA L., JASMINUM OFFICINALE L. AND URTICA DIOICA L.: IMPORTANCE IN FOLK MEDICINE AND PHARMACEUTICALS (Scientific journal of the Fergana State University, 2026)
Medicinal plants are valuable sources of bioactive compounds with potential therapeutic applications. This study focuses on the chemical composition and antioxidant potential of three medicinal species: Matricaria chamomilla L., Jasminum officinale L., and Urtica dioica L. The main objective was to identify their key phytochemical constituents and evaluate their antioxidant and neuroprotective properties.Phytochemical analysis confirmed the presence of flavonoids, phenolic compounds, essential oils, and vitamins (C and K), along with neuroactive phytoestrogens. Chromatographic techniques, including GC–MS and HPLC, were employed to determine the qualitative and quantitative composition of the bioactive compounds. Antioxidant activity was assessed using DPPH, FRAP, and adrenaline autoxidation assays.The results indicated a high concentration of antioxidant compounds in all three species. M. chamomilla and J. officinale demonstrated pronounced neuroprotective and anxiolytic effects, whereas U. dioica exhibited significant benefits for cerebral circulation and oxidative balance.In conclusion, the findings confirm the strong antioxidant and neuroprotective potential of these medicinal plants and support their further investigation as promising natural agents for preventing or managing nervous system disorders.